Evaluasi KJP terhadap Ketepatan Sasaran melalui Pembaruan Data dan Perbaikan Birokrasi - Haris Danadhyaksa; Livia Audy Salsabila; Zafira Adzra Daffany; Fatkhuri Fatkhuri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the evaluation of the Jakarta Smart Card (Kartu Jakarta Pintar/KJP) program in improving the accuracy of educational assistance distribution through data updating and bureaucratic reform in DKI Jakarta Province. The research was motivated by continuing problems related to mistargeted beneficiaries, administrative inefficiency, and weaknesses in the integration of social welfare data. This study uses a qualitative method with a descriptive-evaluative approach. Data were collected through documentation studies and literature reviews from journals, government reports, regulations, and previous studies related to educational social assistance and e-government implementation. The findings show that the implementation of e-government through digital platforms such as SIDEWI and e-hibahbansosdki has contributed to improving transparency and accountability in KJP distribution. However, the program still faces several challenges, including inclusion error, exclusion error, outdated social welfare databases, overlapping administrative procedures, and weak inter-agency coordination. The study also found that bureaucratic complexity and the lack of regular data updates significantly affect the accuracy of beneficiary targeting. Therefore, strengthening data integration, simplifying administrative procedures, improving technological infrastructure, and conducting periodic data validation are necessary to enhance the effectiveness of the KJP program in supporting equitable access to education for low-income communities in DKI Jakarta.